Wittgenstein and the End of Philosophy - Hutto, D. author. aut Link
XII, 261 p.
Keywords: What is the true worth of Wittgenstein's contribution to philosophy? Opinions are strongly divided, with many resting on misreadings of his purpose. This book challenges 'theoretical' and 'therapeutic' interpretations, proposing that Wittgenstein saw clarification as the true end of philosophy, that his approach exemplifies critical philosophy.